Energy-efficiency priority based beamforming design and optimization in IRS-assisted SWIPT system - Xiaorong XU; Weiwei ZHU; Jianrong BAO; Weiping ZHU; Wei FENG; Yingbiao YAO (Dianxin kexue)
Intelligent reflecting surface (IRS)-assisted simultaneous wireless information and power transfer (SWIPT) system is set as research background.Joint design and optimization of energy-efficiency priority based active beamforming at multi-antenna transmitter and passive beamforming at IRS were investigated.The optimization objective was to maximize minimum energy-efficiency, which was subject to transmitter power control, energy constraint at energy harvesting (EH) receiver and IRS phase shift constraint.Alternating direction method of multipliers (ADMM) was implemented to solve this non-linear non-convex optimization problem.Firstly, the fraction objective function was transformed via Dinkelbach’s approach.Singular value decomposition (SVD) andsemi-definite relaxation (SDR) were applied to obtain active beam forming vector at transmitter.Simulation results indicate that, IRS assisted SWIPT could significantly reduce energy threshold at EH receiver.The achievable energy-efficiency of the proposed strategy is 300 KB/J when total circuit power consumption is -15 dBm.Maximum energy-efficiency can be achieved with the maximum numbers of passive reflecting elements and transmitter antennas.